THE FAIR AND EQUITABLE TREATMENT STANDARD IN UZBEKISTAN’S BILATERAL INVESTMENT TREATIES: LIABILITY AND REFORM - Abdulazizova Madinabonu Azizbek qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines the fair and equitable treatment (FET) standard as formulated across Uzbekistan’s bilateral investment treaty (BIT) network. Despite concluding over fifty BITs with major capital-exporting states, Uzbekistan remains largely absent from investment arbitration scholarship, and its FET provisions vary considerably in legal structure and effect. Through a typological survey of Uzbekistan’s BIT practice, the article identifies distinct formulations of the FET clause and maps the differing liability exposures each creates. Particular attention is given to three areas of heightened risk: the protection of legitimate expectations in the energy and natural resources sectors, investor stability claims arising from Uzbekistan’s post-2017 regulatory reforms, and administrative transparency obligations. Drawing on comparative arbitral practice from Central Asian jurisdictions, the article advances three targeted drafting reform recommendations – a closed-list FET formulation, express anchoring to the customary minimum standard of treatment, and a right-to-regulate clause – supported by proposed model treaty language.